THE EFFECT OF WORK MOTIVATION, ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT CV ANDI OFFSET YOGYAKARTA - Melysa Purba; Riko Gesmani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This research is entitled the influence of work motivation, organizational culture and work environment on employee performance at CV. Andi Offset Yogyakarta. The purpose of this research is to determine whether work motivation, organizational culture, and work environment have a partial and simultaneous effect on employee performance. In this study, the author used primary and secondary data. The sampling method used is Simple Random Sampling with a sample of 100 respondents. The analytical tools used include validity and reliability tests, percentage analysis, classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test), simple regression test, t-test, F-test, and coefficient of determination test (R2). Based on the analysis results conducted, it indicates that partially work motivation has a significant effect on employee performance, organizational culture has a significant effect on employee performance, and work environment has a significant effect on employee performance.